Financial fragility and its relationship to financial performance-A comparative study between a sample of private commercial banks listed on the Iraq Stock Exchange - Hadi Hamad Hadi (Global Scientific Publishing, 2023)
Analyzing the reality of the financial fragility of the financial system, especially the banking system, is recent, as it has become an increasingly important goal in the context of making macroeconomic policies, especially its financial and monetary sides, and among the reasons why attention is directed towards the issue of the fragility of the financial system and that it has priority among the interests of financial policy makers. And monetary and economic around the world is the need for sudden financing operations, especially investment, which necessitated a study and nalysis of the impact of the reality of the fragility of the financial system in Iraq on the state and the possibility or ability of the country’s financial and banking system to face the necessary financing operations, especially the local investment ones, and reflects the fragility of the financial system On the state of deterioration and instability of the financial system, whether the banking side of it (i.e. financial and banking institutions), or the financial markets side, in a manner in which it does not perform its functions efficiently, especially the allocation of resources and directing them or making them ready for any sudden financing that can help the economic situation in the country.
Keywords: Financial fragility; financial performance.